SrBi2(Ta0.5Nb0.5)(2)O-9 : W thin films obtained by chemical solution deposition: Morphological and ferroelectric characteristics - Amsei Junior, N. L. [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Cavalcante, L. S.; Moura, E. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V. Sa, 2008)
The effect of tungsten (W6+) ion substituting on dielectric and ferroelectric behavior in SrBi2(Ta0.5Nb0.5)(2)O-9 (SBTN) thin films prepared by polymeric precursor method was investigated at room temperature. The addition of W6+ ion in the SBTN lattice was evaluated by X-ray diffraction (XRD), microstructural and dielectrical properties. An increase in the grain size is evident when tungsten is introduced in the SBTN lattice. Substitution of tungsten until 10% on B site leads to introduce space charge polarization into the system, resulting in an appreciable decrease in both dielectric constant and tangent loss. The morphology of the thin films investigated by atomic force microscopy leads to an increase in the grain size after tungsten addition. Fatigue resistance was noted with increase in tungsten addition. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: thin films; ferroelectrics; chemical synthesis; atomic force microscopy; dielectric response